Factors Associated with the Incidence of Hypertension Among Employees of PT. X in South Jakarta in 2025 - Ekky Pinesti; Erna Veronika (Jurnal EduHealth, 2026)
Hypertension remains one of the most common occupational health problems and may reduce employee productivity, quality of life, and overall well-being. This study aimed to analyze the factors associated with the incidence of hypertension among employees of PT. X in South Jakarta. The study applied a quantitative method with a cross-sectional design. Data were collected through questionnaires, anthropometric measurements, and company medical check-up records. The variables examined included age, physical activity, Body Mass Index, smoking habits, workload, and work stress. Data analysis was conducted using univariate and bivariate statistical tests to identify the relationships between independent variables and hypertension incidence. The findings showed that hypertension was highly prevalent among employees. Age, Body Mass Index, and smoking habits were significantly associated with hypertension incidence, indicating that biological and lifestyle-related factors play important roles in increasing hypertension risk among workers. Meanwhile, physical activity, workload, and work stress were not significantly associated with hypertension incidence. The study concludes that hypertension among employees is influenced by multifactorial conditions, particularly modifiable lifestyle factors. Therefore, workplace health promotion programs, regular health screening, smoking cessation interventions, nutrition education, and healthy lifestyle campaigns should be strengthened to improve employee health and reduce the risk of hypertension in the workplace.